Regrow Napier grass–Chinese milk vetch relay intercropping system: A cleaner production strategy in Cd-contaminated farmland. (10th March 2022) - Qin, Jianjun; Long, Jian; Peng, Peiqin; Huang, Jing; Tang, Shengshuang; Hou, Hongbo
Abstract: The cultivation methods determine the production and remediation capacity of crops in heavy metal-contaminated farmland. This study investigated the effects of seedling establishment methods and relay intercropping with Chinese milk vetch ( Astragalus sinicus L., CMV) on the production and remediation of Napier grass ( Pennisetum purpureum Schum, NG) in cadmium (Cd)-contaminated farmland in southern China. The results showed that the regrow NG (RNG) had higher aerial part yield because of its well-developed roots and larger tiller numbers, which increased the Cd uptake. CMV mulching promoted the stubble seedling's growth by increasing the soil temperature during the overwintering period. The CMV return to field increased the soil dissolved organic carbon (DOC), enhanced the bioavailability of Cd in soil, and promoted the Cd uptake of NG. The CMV application also alleviated the total nitrogen decline of soil. The CMV–RNG relay intercropping system (CMV–RNG) produced larger aerial part yield and Cd uptake, mowing NG once (in December), reaching 60.60 t ha −1 (DW) and 29.09 g ha −1, respectively, and August was the suitable month to mow for higher yield and Cd uptake. Meanwhile, the Cd concentration in NG aerial parts was relatively low (0.16–0.59 mg kg −1 ), making it safe to be used as fodder. Thus, the CMV–RNG system is a cleaner production strategy in Cd-contaminated farmland. Graphical abstract: Image 1 Highlights: Relay intercropping with Chinese milk vetch could promote Napier grass overwintering. Returning Chinese milk vetch to the field increased total nitrogen and available Cd. Regrow Napier grass has a very high Cd removal capacity due to its huge biomass.